The Time of the Sign A Semiotic Interpretation of Modern Culture - MacCannell, Juliet Flower (Indiana University Press, 1982)
A sociologist-anthropologist and a literary critic bring their complementary perspectives to bear on a critique of modern culture. They point to the academy's domination by a rationalist, liberal tradition as the locus of its decline in the post-modern era. A holistic, semiotic approach is offered as a vital and positive alternative. The book builds and expands on the authors' modified Saussurian model for the analysis of culture presented in the opening section. Part Two explores the implications of the general model for the social sciences and includes a discussion of Marx and Freud after semiotics; Part Three addresses literary and cultural criticism. The penultimate chapter, "On the Discriminations of Signs," reviews the recent historical evolution of intellectual schools of thought, from phenomenology through existentialism, structuralism, post-structuralism, and semiotics. It regards this evolution from the standpoint of the successive transformations of our understanding of "the sign." The book concludes with a critique of counterrevolutionary tendencies that have recently surfaced within semiotics. The Time of the Sign is an invigorating and probing work, with many acute insights into the development and analysis of cultural forms.